Implementasi Pembelajaran Mendalam di Madrasah Ibtidaiyah: Studi Kualitatif tentang Perencanaan, Pelaksanaan, dan Faktor Pendukung - Muhammad Khaidil; Amirul Mukminin; Kiki Fatmawati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The national education transformation through the Merdeka Curriculum demands a paradigm shift from material-based teaching to student-centered learning. One adopted approach is deep learning, which emphasizes comprehensive concept mastery, critical thinking, reflection, and knowledge application in real-world contexts. This study aims to analyze the implementation of deep learning in Madrasah Ibtidaiyah, covering planning, execution, and supporting and inhibiting factors. Using a qualitative case study approach at MI Nurul Hidayah, Jambi City, data were collected through observation, in-depth interviews, and documentation involving the madrasah head, curriculum deputy, teachers, and students. Data analysis employed the interactive model of Miles, Huberman, and Saldaña. The findings reveal that implementation has commenced through the development of active learning tools and contextual learning experiences. Supporting factors include teachers' pedagogical competence, institutional policy support, and learning facilities. Meanwhile, inhibiting factors include students' heterogeneous abilities, time constraints, and teachers' uneven understanding of deep learning. This study provides empirical contributions for developing meaningful learning in primary education, particularly at the Madrasah Ibtidaiyah level